2015
DOI: 10.1051/0004-6361/201425036
|View full text |Cite
|
Sign up to set email alerts
|

TheGaia-ESO Survey: Kinematics of seven Galactic globular clusters

Abstract: The Gaia-ESO survey is a large public spectroscopic survey aimed at investigating the origin and formation history of our Galaxy by collecting spectroscopy of representative samples (about 10 5 Milky Way stars) of all Galactic stellar populations, in the field and in clusters. The survey uses globular clusters as intra-and inter-survey calibrators, deriving stellar atmospheric parameters and abundances of a significant number of stars in clusters, along with radial velocity determinations. We used precise radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 80 publications
9
61
2
Order By: Relevance
“…They find a mean radial velocity of v r = 75.9 ± 0.3 km s −1 and a central velocity dispersion of σ 0 = 4.5 ± 0.3 km s −1 . As part of the Gaia-ESO survey, the kinematics of seven GGCs is present in Lardo et al (2015). Using FLAMES/GIRAFFE they analyzed spectra of more than 100 stars and obtained a mean radial velocity of v r = 75.2 ± 0.4 km s −1 with a velocity dispersion of 3.9 km s −1 , confirming the membership of our objects.…”
Section: Observations and Data Reductionsupporting
confidence: 74%
“…They find a mean radial velocity of v r = 75.9 ± 0.3 km s −1 and a central velocity dispersion of σ 0 = 4.5 ± 0.3 km s −1 . As part of the Gaia-ESO survey, the kinematics of seven GGCs is present in Lardo et al (2015). Using FLAMES/GIRAFFE they analyzed spectra of more than 100 stars and obtained a mean radial velocity of v r = 75.2 ± 0.4 km s −1 with a velocity dispersion of 3.9 km s −1 , confirming the membership of our objects.…”
Section: Observations and Data Reductionsupporting
confidence: 74%
“…and±30°for PAo. Compared to the large globular cluster samples presented in Bellazzini et al (2012), Kimmig et al (2015), and Lardo et al (2015), NGC 6273 exhibits relatively strong rotation. NGC 6273ʼs large A rot.…”
Section: Cluster Rotationmentioning
confidence: 86%
“…Additional velocity measurements inside ∼0 2-0 5 and the application of more sophisticated models are likely to find a true σ o >12 kms 1 . We estimate that the cluster's true Arot./σ o ratio is ∼0.30-0.35, which is typical for massive elliptical metal-poor globular clusters (e.g., see Bellazzini et al 2012;Kacharov et al 2014;Kimmig et al 2015;Lardo et al 2015).…”
Section: Cluster Rotationmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, deviations from the sharply truncated King phase space distribution (e.g., see the cases of NGC 1851, as studied by Olszewski et al 2009;Marino et al 2014, NGC 5694 by Correnti et al 2011;Bellazzini et al 2015, and several others, as discussed, e.g., by Carballo-Bello et al 2018), spherical symmetry (e.g., Chen & Chen 2010), and pressure isotropy (e.g., van de Ven et al 2006;Bellini et al 2014Bellini et al , 2017Watkins et al 2015) are found in a growing number of GGCs. Also the observational evidence of systemic rotation is increasing (e.g., Anderson & King 2003;Lane et al 2009Lane et al , 2010Bellazzini et al 2012;Bianchini et al 2013;Fabricius et al 2014;Kacharov et al 2014;Kimmig et al 2015;Lardo et al 2015;Bellini et al 2017;Boberg et al 2017;Cordero et al 2017;Ferraro et al 2018b;Kamann et al 2018), possibly suggesting that, when properly surveyed, the majority of GCs rotate at some level. In particular, Ferraro et al (2018b) investigated the intermediate/external region of 11 clusters, demonstrating the presence of internal rotation in almost all of them.…”
Section: Introductionmentioning
confidence: 99%